Analysis of Methods and Technologies for Composition Assessing of Corium Formed as a Result of the Fukushima Daiichi NPP Accident - S. N. Ryzhov; E. V. Bogdanova; A. A. Ryzhkov; P. A. Pugachev; G. V. Tikhomirov; M. Yu. Ternovykh; T. B. Aleeva (Глобальная ядерная безопасность)
This paper analyzes the methods and technologies for assessing the method of formation, composition, characteristics and features of corium, which is a mixture of nuclear and structural materials of the nuclear reactor core, formed as a result of an accident accompanied by partial or complete core melting. The study is based on data from the study of corium formed as a result of the accident at the Fukushima Daiichi nuclear power plant, which are in the public domain and are the result of the work of many scientific organizations around the world. Corium research is one of the main issues in the framework of improving nuclear safety in the future and is one of the objectives of the successful procedure for eliminating the consequences of the accident at the Fukushima Daiichi nuclear power plant. Without a detailed analysis of the neutronic, materials science, gravimetric and other characteristics of the corium, as well as the creation of a complex model of the corium that combines these data, it is impossible to organize an efficient and safe process for removing nuclear materials from the damaged units of the Fukushima Daiichi nuclear power plant. The objective of this work is to combine the existing research results into a data set that allows modeling of the corium using neutronic calculation codes and includes such data as the size, density and morphology of corium samples and their approximate nuclide composition. Such modeling allows not only to perform tasks related to increasing the level of safety in the implementation of the procedure for eliminating the consequences of the accident at the Fukushima Daiichi nuclear power plant, but also to serve as an international benchmark for modeling a mixture containing nuclear materials.